Turning Points (De Gruyter, 2012)
At times of crisis and revolution such as ours, diagnoses of crucial junctures and ruptures - 'turning points' - in the continuous flow of history are more prevalent than ever. Analysing literary, cinematic and other narratives, the volume seeks to understand the meanings conveyed by different concepts of turning points, the alternative concepts to which they are opposed when used to explain historical change, and those contexts in which they are unmasked as false and over-simplifying constructions. Literature and film in particular stress the importance of turning points as a sensemaking device (as part of a character's or a community's cultural memory), while at the same time unfolding the constructive and hence relative character of turning points. Offering complex reflections on the notion of turning points, literary and filmic narratives are thus of particular interest to the present volume
10.1515/9783110297102
Keywords: Change in literature; Mass media and history; Social change in literature; Narratology; Time; Wendepunkte; Zeitkonzepte; narratology; LITERARY CRITICISM / General